Factors influencing on selecting of research topics: Case study of Fourth-year undergraduate, Academic year 2018, Thai language students, Faculty of Liberal Arts, University of Phayao - Yingyongsak, Warunya (Trends of Humanities and Social Sciences Research, 2020)
The purpose of this research was to analyze factors influencing on selecting the research topics of the Fourth-year undergraduate, Academic year 2018, Thai language students, Faculty of Liberal Arts, University of Phayao. The instrument of this research was a set of questionnaire. The participants of this study were the Fourth-year undergraduate, Academic year 2018, Thai language students, Faculty of Liberal Arts, University of Phayao. The samples were selected by using purposive sampling; 137 students. The data were analyzed by frequency, percentage, mean, and standard deviation. To know the factors influencing the research topic selection of students and have analyzed the results into data to guide and develop teaching and learning correctly and appropriately in accordance with the needs of learners. The results showed that Background information revealed that most of the respondents were female 85.40%; male 14.60%, aged were 22 yrs 72.26%; 21 yrs 27.74%, GPA was between 3.01 and 3.50 45.99%, and the most favorite and good at courses were Literature 39.42. Factors influencing on selecting the research topics showed that the most influencing factor was Independent Study Advisor factor with mean score at the high level (= 4.09), followed by Students factor with mean score at the high level (= 3.99), Environment and Current Values factor with mean score at the high level (= 3.91), and the lowest influencing factor was Friends and Seniors factor with the mean score at the low level (= 2.40), respectively.